Correlation of Serum Lactate and Shock Index as Mortality Predictor in Polytrauma Patients: Serum Lactate and Shock Index in Polytrauma Patients - Siddiqui, Noor us Sahar; Ahmed, Meer; Sikhandar, Sanober; Shakoor, Soonh; Memon, Shahdil Zulfikar; Khan, Muhammad Momin; Mushtaq, Saima (Pakistan Journal of Health Sciences, 2024)
In polytrauma patients, serum lactate and hypovolemic shock are critical biomarkers for prognosis and treatment guidance. Elevated lactate levels indicate tissue hypoperfusion and anaerobic metabolism, often correlating with increased mortality. Objective: To analyze the correlation between serum lactate levels and shock index as predictors of in-hospital mortality in polytrauma patients. Methods: A Cohort study was conducted from August 2022 to July 2023 at a single tertiary care hospital in Karachi. Patients were chosen via consecutive sampling techniques and included adult patients with polytrauma injuries (ISS ≥ 15) who survived at least 24 hours. Patients with a history of diabetes were excluded. The serum lactate levels and shock index at the time of admission and over the first 24 hours were the exposures while in-hospital mortality, was the primary outcome. Statistical analyses were conducted using Stata 16.0. Categorical variables were analyzed using the chi-square test. Multivariable logistic regression evaluated mortality risk, adjusting for age, ISS, and shock index. Results: The in-hospital mortality rate in the study was 6.4% with significant predictors of mortality included increasing age (47.05 vs. 27.62 years, p<0.001), higher Injury Severity Scores (ISS) (24 vs. 19, p= 0.02), and elevated shock index at admission (0.84 vs. 0.71, p<0.001). Lactate metrics were strongly associated with mortality, showing significant correlations. Conclusions: Higher serum lactate levels and shock index are strong predictors of mortality in polytrauma patients. Greater age and injury severity also contribute to poorer outcomes.